Pentingnya Penggunaan Teknologi Informasi dan Komunikasi dalam Menunjang Pembelajaran Sekolah Dasar - Yohannes Marryono Jamun; Zephisius Rudiyanto Eso Ntelok; Rudolof Ngalu (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Information and Communication Technology (ICT) plays a crucial role in the current educational context, and it must be introduced by teachers to their students. Teachers in this 4.0 era of Education need to adapt to this rapidly. The use of ICT in teaching helps explain challenging and abstract materials in a more tangible and contextual way. Additionally, it aims to overcome communication barriers between educators and learners. The objective of this research is to explore a deep understanding of the importance of ICT in the context of elementary school education. The research method used is a literature review based on the analysis and synthesis of information sources available in the literature or references that are relevant to this research topic. The research results explain that use of ICT as a learning tool in elementary schools has a positive impact on students' learning achievements and can stimulate their interest in learning. The use of ICT also enables more flexible and effective learning in improving the quality of education. However, there are challenges, including the lack of infrastructure and teacher readiness. Nevertheless, the use of ICT at the elementary school level holds great potential for enhancing the quality of education. Therefore, efforts are needed to improve access to the use of ICT in education.